2017
DOI: 10.1017/wet.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-Induced Antagonism in Rapid Response Giant Ragweed (Ambrosia trifida)

Abstract: Glyphosate application to the rapid-response (RR) biotype of glyphosate-resistant (GR) giant ragweed ensues in loss of foliage via rapid tissue death, thereby reducing glyphosate translocation. Experiments were performed to determine if this GR response, in contrast to a non-rapid response (NRR) GR biotype, results in antagonism of the selective herbicides atrazine, cloransulam, dicamba, lactofen, and topramezone. Application of glyphosate at 1,680 g ae ha–1in the greenhouse resulted in antagonism between all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…However, a mixture of glyphosate plus lactofen provided 79 to 90% control of the RR biotype in a field trial and, when compared with several commonly used selective herbicides in Z. mays and G. max production, was one of the few in which the glyphosate‐induced RR did not antagonize efficacy. Collectively, these results indicate that such herbicides remain viable control options and RR A. trifida is not inherently more tolerant to oxidative stress than GS A. trifida .…”
Section: Resultsmentioning
confidence: 96%
“…However, a mixture of glyphosate plus lactofen provided 79 to 90% control of the RR biotype in a field trial and, when compared with several commonly used selective herbicides in Z. mays and G. max production, was one of the few in which the glyphosate‐induced RR did not antagonize efficacy. Collectively, these results indicate that such herbicides remain viable control options and RR A. trifida is not inherently more tolerant to oxidative stress than GS A. trifida .…”
Section: Resultsmentioning
confidence: 96%
“…Previous work has shown that increasing glyphosate rates from 420 to 1,680 g ha −1 causes the RR to be induced sooner (Harre et al 2017a). Moreover, work on both NRR and RR biotypes of GR A. trifida has shown that increasing glyphosate rates when applied with POST herbicides improves efficacy on the NRR biotype, yet reduces efficacy on the RR biotype (Harre et al 2017b). Collectively, these results suggest that any factor that more quickly elicits induction of the RR will have the propensity to antagonize translocated POST herbicides, highlighting the importance of knowing which biotypes of GR A. trifida are present in fields.…”
Section: Resultsmentioning
confidence: 99%
“…In geographies affected by GR weeds, application of POST herbicides in combination with glyphosate has become routine practice for many grain producers to broaden the spectrum of weed control and employ additional mechanisms of action to manage GR biotypes (Benbrook 2016). However, in both field and greenhouse studies, the glyphosate-induced RR in A. trifida can antagonize the efficacy of glyphosate mixtures with atrazine, cloransulam, dicamba, and topramezone (Harre et al 2017b). Furthermore, at increasing glyphosate rates, the RR elicits greater H 2 O 2 production in leaf tissue, thereby amplifying the degree of glyphosate-induced antagonism on POST herbicides (Harre et al 2017a(Harre et al , 2017b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid resistance evolution to glyphosate highlights the relevance of implementing different weed management strategies (Ganie and Jhala, 2017). In general, the mixtures of the alternative herbicide with glyphosate showed additive effects, because synergistic interactions between agrochemicals are rare (Cedergreen, 2014), and it is more common to observe antagonistic effects of glyphosate mixed with herbicides, such as atrazine, cloransulam, dicamba, lactofen, and topramezone (Vidal et al, 2003;Harre et al, 2018). Additive effects were observed in most mixtures, and explain why those herbicides that showed lower (carfentrazone-ethyl, flumioxazin and oxyfluorfen) or intermediate (fluroxypyr, MCPA and 2,4-D) control in GR Conyza species when they were applied alone, continued to show inefficient control when applied in mixture with glyphosate, since the control increase observed with the mixtures of these herbicides was proportional to that obtained by glyphosate alone.…”
Section: Chemical Control Of Glyphosate-resistant Populations Of Conymentioning
confidence: 99%